The Nexus Between Zakat Performance, COVID-19 crisis and Islamic Banks’ Profitability: Empirical evidence from Indonesia - Sulaeman Sulaeman; Muhammad Adam; Indri Supriani (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
This paper aims to empirically analyse the nexus between zakat performance, the COVID-19 crisis, and Islamic banks' profitability in Indonesia from 2015 to 2021. This study applied a quantitative method from the panel data regression model. The secondary data was used with a total sample of 10 selected Indonesian Islamic commercial banks. Based on the empirical findings, zakat performance is the primary determinant of Islamic banks' profitability in Indonesia. This is proven that zakat contributes significantly to increasing Islamic banks' profitability, namely ROA, ROE, and NPM. Further, another finding regarding the dummy crisis variable, the COVID-19 crisis (COVID-19), finds a strong effect on the Islamic banks' profitability in Indonesia, namely ROA and NPM. Our empirical study provides implications for developing literature and directing policy recommendations for zakat institutions such as BAZNAS, LAZ, and Islamic banks management. Further research is needed to observe the zakat performance and the longer period of the COVID-19 crisis impact on Islamic banks' profitability in Indonesia.